Lack of Belonging Predicts Depressive Symptomatology in College Students. (July 2022) - Dutcher, Janine M.; Lederman, James; Jain, Megha; Price, Stephen; Kumar, Agam; Villalba, Daniella K.; Tumminia, Michael J.; Doryab, Afsaneh; Creswell, Kasey G.; Riskin, Eve; Sefdigar, Yasaman; Seo, Woosuk; et al.
Feeling a sense of belonging is a central human motivation that has consequences for mental health and well-being, yet surprisingly little research has examined how belonging shapes mental health among young adults. In three data sets from two universities (exploratory study: N = 157; Confirmatory Study 1: N = 121; Confirmatory Study 2: n = 188 in winter term, n = 172 in spring term), we found that lower levels of daily-assessed feelings of belonging early and across the academic term predicted higher depressive symptoms at the end of the term. Furthermore, these relationships held when models controlled for baseline depressive symptoms, sense of social fit, and other social factors (loneliness and frequency of social interactions). These results highlight the relationship between feelings of belonging and depressive symptoms over and above other social factors. This work underscores the importance of daily-assessed feelings of belonging in predicting subsequent depressive symptoms and has implications for early detection and mental health interventions among young adults.